In vitro study of the treatment of dentin hypersensitivity with gallic acid combined with sodium fluoride - Xiao Han; Wenjiao Zheng; Jinping Zhao; Shan Xu; Yao Shi (BMC, 2024)
Abstract Background Dentin hypersensitivity (DH) is a common oral condition that is associated with severe dental pain. Pain relief is a key focus of the treatment of DH. The purpose of this study was to evaluate the blocking and antacid effects of gallic acid (GA) combined with sodium fluoride (NaF) on dentinal tubules in vitro. Methods Ninety dentin discs from human third molars were treated with 6% citric acid for 2 min. Then, the surface morphologies of ten dentin discs were observed by scanning electron microscopy (SEM). The remaining samples were randomly divided into four groups: the NaF group, which was treated with 1000 ppm NaF; the GA group, which was treated with 4000 ppm GA; the GA + NaF group, which was treated with 1000 ppm NaF + 4000 ppm GA; and the blank group, which was treated with deionized water. The dentin permeability of each sample was measured with a water-filled system before processing and after 7 days of treatment. Dentin morphology and surface deposits were observed by SEM. Then, samples from the NaF, GA + NaF and blank groups were subjected to an acid challenge by incubation with 0.02% citric acid for 2 min. SEM and a water-filled system were used to evaluate the blocking and antacid effects of NaF and GA + NaF. Results 1. NaF and GA + NaF significantly decreased dentin permeability. The effect of the GA + NaF treatment was more significant. After acid challenge, both groups still exhibited decreased dentin permeability compared with the initial assessment. 2. Compared with the NaF group, the GA + NaF group had more mineral deposits on the dentin surface and dentin tubules. After acid challenge, the deposits in the GA + NaF group were still clearly visible. Conclusion The combined effect of GA and NaF on reducing dentin permeability by blocking open dentin tubules is better than that of NaF alone. After acid challenge, the GA + NaF treatment still had a better effect.